Factors Affecting Science Research Motivation of Lecturers of Hanoi University - Thuong, Le Thi (VNU Journal of Science: Education Research; Vol 36 No 3DO - 10.25073/2588-1159/vnuer.4433, 2020)
By synthesizing domestic and foreign studies related to the scientific research motivation of lecturers, considering the factors of studies models, inheriting suitable research results to build model of factors influencing to the scientific research motivation of lecturers of Hanoi University. This study applied factor analysis (EFA) to explore the factors affecting the motivation of scientific research based on a dataset of 218 teacher responses. At the same time, the research conducted in-depth interviews with 09 lecturers at Hanoi University. The analysis results show that the proposed factors in the model have different influence on the scientific research motivation of Hanoi University lecturers including: Professional competence of lecturers, Lecturer's social issues, Research environment, School’s support for scientific research activities and Lecturers' awareness of scientific research. These factors explained 61.81% of the influence on the scientific research motivation of lecturers.